The saga of participatory forest management in India - Saxena, N.C. (Center for International Forestry Research, 1997)
After about a hundred years of exclusive government control, forests in India are now being increasingly managed with people’s participation. Almost all states in India have passed enabling resolutions to facilitate what is now popularly called the Joint Forest Management (JFM) programme. However, its implementation has so far been uneven. Field officers are often loath to share power and authority with the people, while expecting them to protect forests without wages. It is also not very well known under what conditions JFM succeeds, and whether these conditions are internal or more influenced by governmental policies. Based on the author’s repeated visits to JFM villages in several Indian states, this book provides a critique of the past and current forest policies, reviews the implementation of participatory forest management in five Indian states, explains why communal action is sustained over time, and places its conclusions in the wider theory of property regimes. The book attempts a synthesis of diverse experiences in participation and links hypotheses of collective action with empirical evidence. One of the first source books on Joint Forest Management, it will be of value to donor agencies, state governments, policy makers and researchers on participatory development programmes